Dextran sulfate sodium and 2,4,6-trinitrobenzene sulfonic acid induce lipid peroxidation by the proliferation of intestinal gram-negative bacteria in mice - Hyun Yang-Jin; Bae Eun-Ah; Lee In-Ah; Kim Dong-Hyun (BMC, 2010)
Abstrect Background To understand whether TLR-4-linked NF-kB activation negatively correlates with lipid peroxidation in colitic animal models, we caused colitis by the treatment with dextran sulfate sodium (DSS) or 2,4,6-trinitrobenzenesulfonic acid (TNBS) to C3H/HeJ (TLR-4-defective) and C3H/HeN (wild type) mice, investigated inflammatory markers, lipid peroxidation, proinflammatory cytokines and TLR-4-linked NF-κB activation, in colon and intestinal bacterial composition in vivo. Methods Orally administered DSS and intrarectally injected TNBS all caused severe inflammation, manifested by shortened colons in both mice. These agents increased intestinal myeloperoxidase activity and the expression of the proinflammatory cytokines, IL-1β, TNF-α and IL-6, in the colon. Results DSS and TNBS induced the protein expression of TLR-4 and activated transcription factor NF-κB. However, these colitic agents did not express TLR-4 in C3H/HeJ mice. Of proinflammatory cytokines, IL-1β was most potently expressed in C3H/HeN mice. IL-1β potently induced NF-κB activation in CaCo-2 cells, but did not induce TLR-4 expression. DSS and TNBS increased lipid peroxide (malondialdehyde) and 4-hydroxy-2-nonenal content in the colon, but reduced glutathione content and superoxide dismutase and catalase activities. These colitic inducers increased the number of Enterobacteriaceae grown in DHL agar plates in both mice, although the number of anaerobes and bifidobacteria grown in GAM and BL agar plates was reduced. E. coli, K. pneumoniae and Proteus mirabilis isolated in DHL agar plates increased lipid peroxidation in liposomes prepared by L-α-phosphatidylcholine, but B. animalis and B. cholerium isolated from BL agar plates inhibited it. Discussion These findings suggest that DSS and TNBS may cause colitis by inducing lipid peroxidation and enterobacterial proliferation, which may deteriorate the colitis by regulating proinflammatory cytokines via TLR-4-linked NF-κB activation pathway.